Antibacterial Activity of Aureonuclemycin Produced by Streptomyces aureus Strain SPRI-371 - Weiguo Wang; Minkang Feng; Xiaomeng Li; Feiyu Chen; Zhihao Zhang; Wenlong Yang; Chen Shao; Liming Tao; Yang Zhang (Molecules, 2022)
Actinomycetes play a vital role as one of the most important natural resources for both pharmaceutical and agricultural applications. The actinomycete strain SPRI-371, isolated from soil collected in Jiangsu province, China, was classified as Streptomyces aureus based on its morphological, physiological, biochemical and molecular biological characteristics. Its bacterial activity metabolites were identified as aureonuclemycin (ANM), belonging to adenosine derivatives with the molecular formula C16H19N5O9 for ANM A and C10H13N5O3 for ANM B. Simultaneously, the industrial fermentation process of a mutated S. aureus strain SPRI-371 was optimized in a 20 m3 fermentation tank, featuring a rotation speed of 170 rpm, a pressure of 0.05 MPa, an inoculum age of 36–40 h and a dissolved oxygen level maintained at 1–30% within 40–80 h and at >60% in the later period, resulting in an ANM yield of >3700 mg/L. In the industrial separation of fermentation broth, the sulfuric acid solution was selected to adjust pH and 4# resin was used for adsorption. Then, it was resolved with 20% ethanol solution and concentrated in a vacuum (60–65 °C), with excellent results. Antibacterial experiments showed that ANM was less active or inactive against Xanthomonas oryzae pv. oryzae, Xanthomonas citri subsp. citri and Xanthomonas oryzae pv. oryzicola and most bacteria, yeast and fungi in vitro. However, in vivo experiments showed that ANM exhibited extremely significant protective and therapeutic activity against diseases caused by X. oryzae pv. oryzae and X. oryzae pv. oryzicola in rice and X. citri in oranges and lemons. In field trials, ANM A 150 gai/ha + ANM B 75 gai/ha exhibited excellent therapeutic activity against rice bacterial leaf blight, citrus canker and rice bacterial leaf streak. Furthermore, as the dosage and production cost of ANM are lower than those of commercial drugs, it has good application prospects.